A comparative study on palmprint recognition - Mohammed, Hayman Salih (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Palmprint recognition uses the palm of a person as a biometric for identifying or verifying the human beings. The palmprint contains a number of distinctive features such as principal lines, wrinkles, ridges and minutiae. Therefore, it is appropriate to use feature extraction techniques in order to extract line, texture, statistics and multiple representations. This thesis presents a comparative study on palmprint recognition using different approaches to extract palmprint features. Appearance-based approaches such as Principal Component Analysis, statistical approaches such as Local Binary Patterns, transform-based approaches such as Discrete Cosine Transform and other approaches such as Log-Gabor filters have been investigated and evaluated on PolyU palmprint database. The experimental results on both right and left palmprint databases demonstrate that Local Binary Patterns approach is a good texture descriptor which achieves the best recognition accuracy compared to other methods. Keywords: Log-Gabor, Discrete Cosine Transform, Local Binary Patterns, Principal Component Analysis

ÖZ Avuçiçi tanıma insanları tanımlamak veya doğrulamak için biyometrik olarak bir kişinin avuçiçini kullanır. Avuçiçi ana hatlar, kırışıklıklar, sırtlar ve önemsiz ayrıntılar gibi bir dizi ayırt edici öznitelikler içerir. Bu nedenle, öznitelik çıkarma tekniklerini kullanarak uygun bir çizgi, doku, istatistik ve çoklu gösterim elde etmek daha uygundur. Bu tez, avuçiçi özniteliklerini çıkartarak farklı avuçiçi tanıma yaklaşımlarını kıyaslar. Ana Bileşenler Analizi (PCA) gibi görünüm-tabanlı yaklaşımlar, Yerel İkili Örüntü (LBP) gibi doku-tabanlı yaklaşımlar, Ayrık Kosünüs Dönüşümü (DCT) gibi dönüşüm-tabanlı yaklaşımlar ve Log-Gabor filtreleri gibi diğer yaklaşımlar PolyU avuçiçi veritabanı üzerinde incelenmekte ve değerlendirilmektedir. Hem sağ hem de sol avuçiçi veritabanları üzerinde yapılan deney sonuçları, bize Yerel İkili Örüntü yaklaşımının iyi bir doku tanımlama yöntemi olduğu için diğer yöntemlere göre daha başarılı bir performans elde ettiğini göstermektedir. Anahtar kelimeler: Log-Gabor, Ayrık Kosünüs Dönüşümü (DCT), Yerel İkili Örüntü (LBP), Ana Bileşenler Analizi (PCA)
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Assist. Prof. Dr. Önsen Toygar.
Keywords: Computer Engineering; Pattern recognition systems; Image processing; Pattern perception; Log-Gabor; Discrete Cosine Transform; Local Binary Patterns; Principal Component Analysis